Fish Protein Dispersion as a Coating to Prevent Quality Loss in Processed Fishery Products - V., Venugopal; S.V., Sherekar; A.S., Kakatkar (Fishery Technology, 2025)
The conventional technique of water glazing has limitation in protecting the products during prolonged frozen storage. A novel fish protein glaze was devised and its superior protective ability in retarding quality losses of frozen fish items as compared with water glazing is demonstrated. The methodology for fish protein glaze preparation involved soaking of fish meat in pieces in excess cold water followed by soaking in dilute acetic acid to induce hydration of proteins resulting in gel formation. Finally hydrated gel was homogenized in water to get protein dispersion to an apparent viscosity of 1 Pa.s. The fish samples were given a dip in dispersions prepared from the same fish meat. Glazing of frozen mince muscle blocks of Indian mackerel (Rastrelliger kanagurta) by a dispersion prepared from mackerel myofibrillar proteins significantly reduced lipid oxidation and dehydration in the product during sfbrage at -170C. Influence of glazing alone or in combination with low dose gamma irradiation was also examined on the shelf life of seer fish (Scomberomorus guttatus) steaks stored in ice. It was observed that while untreated steaks had a shelf life of 15 days, the steaks displayed extension in shelf of 5 and 15 days when subjected to glazing alone or glazing in combination with gamma irradiation at IkGy respectively.